Research on the coordinated output control strategy of novel DPFC based on multi-objective optimization - Dan, Yangqing; Zhong, Hui; Wang, Jun; Fei, Yanan; Yu, Le; Sun, Licheng (Frontiers in Energy Research, 2025)
To improve power distribution control in systems with multiple Distributed Power Flow Controller (DPFC) sub-units, this study addresses the limitations of conventional strategies such as equal distribution and capacity ratio methods, which often result in low device utilization and high power losses, especially under low line regulation conditions. A novel DPFC topology is analyzed to understand device output characteristics and sub-unit loss mechanisms. Focusing on output voltage and capacity utilization, the research proposes a coordinated output control strategy that comprehensively considers total system losses, utilization rates of sub-units, and operational constraints. Simulation results demonstrate that the proposed method significantly enhances power flow control efficiency and reduces losses compared to traditional approaches, offering improved performance in scenarios with minimal line regulation requirements.